A Formulation of the Industrial Conceptual Design Optimization Problem for Commercial Transport Airplanes - Hikaru Takami; Shigeru Obayashi (Aerospace, 2022)
A realistic industrial conceptual design optimization problem for commercial transport airplanes was formulated with reasonable fidelity and comprehensiveness by selecting appropriate design parameters, constraints, and objectives, in order to provide a baseline to facilitate research on developing robust and efficient optimization methods for the industrial conceptual design of such airplanes. As a sample problem, a multiobjective simultaneous optimization of the design parameters for two types of civil passenger transport airplanes that constitute a family, with identical wing and tail geometries but different performance specifications, was performed using a genetic algorithm coupled with a constraint-handling technique. The results indicated that a realistic industrial conceptual design optimization of commercial transport airplanes, including simultaneous optimization of family airplanes, could be performed with the formulation. The findings from the sample optimization were also presented.